2000
DOI: 10.1007/s004240000318
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen inhibits Ca2+ uptake by the cardiac sarcoplasmic reticulum

Abstract: Ca2+ transients in isolated cardiac ventricular myocytes and the amount of Ca2+ that could be released from the sarcoplasmic reticulum (SR) in these cells by caffeine were reduced in the presence of tamoxifen. To examine the effects of tamoxifen on the cardiac muscle SR directly, isolated SR vesicles and fluorimetry methods were used to measure the uptake of Ca2+ by the SR and the ATPase activity of the SR Ca2+ pump. SR Ca2+ uptake was inhibited by tamoxifen at concentrations greater than 2.4 microM. Half-maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 31 publications
6
45
0
Order By: Relevance
“…These different effects may explain the process of cell death induced by this anticancer agent in different cell types, including ER-negative breast cancer (Jordan 1990), lung adenocarcinoma (Croxtall et al, 1994), prostate cancer (Bergan et al, 1999), ovarian carcinoma (Trope et al, 2000), virus (Laurence et al, 1990), and bacteria (Luxo et al, 1996), since ATP is required to maintain the cell viability. Moreover, our data in isolated mitochondria are according to the ⌬⌿ depolarization induced by TAM either in neurons (Hoyt et al, 2000) or in normal human mammary epithelial cells (Dietze et al, 2001) and may explain the inhibition of Ca 2ϩ uptake by the cardiac sarcoplasmic recticulum (Kargacin et al, 2000) and the TAM-induced inhibition of acidification in ER-independent cells (Altan et al, 1999). The mitochondrial depolarization induced by TAM may be also important as an early event in the promotion of apoptosis, a critical process for normal tissue homeostasis that may be involved in the cytotoxic ER-independent effects of TAM observed in vivo (Dietze et al, 2001).…”
Section: Fig 5 Effects Of Tam (-) Andmentioning
confidence: 65%
“…These different effects may explain the process of cell death induced by this anticancer agent in different cell types, including ER-negative breast cancer (Jordan 1990), lung adenocarcinoma (Croxtall et al, 1994), prostate cancer (Bergan et al, 1999), ovarian carcinoma (Trope et al, 2000), virus (Laurence et al, 1990), and bacteria (Luxo et al, 1996), since ATP is required to maintain the cell viability. Moreover, our data in isolated mitochondria are according to the ⌬⌿ depolarization induced by TAM either in neurons (Hoyt et al, 2000) or in normal human mammary epithelial cells (Dietze et al, 2001) and may explain the inhibition of Ca 2ϩ uptake by the cardiac sarcoplasmic recticulum (Kargacin et al, 2000) and the TAM-induced inhibition of acidification in ER-independent cells (Altan et al, 1999). The mitochondrial depolarization induced by TAM may be also important as an early event in the promotion of apoptosis, a critical process for normal tissue homeostasis that may be involved in the cytotoxic ER-independent effects of TAM observed in vivo (Dietze et al, 2001).…”
Section: Fig 5 Effects Of Tam (-) Andmentioning
confidence: 65%
“…Field stimulation was then stopped and a second caffeine pulse was then applied within 3 s, and the area under the resulting transient was compared with the area under the transient evoked by caffeine during the first (control) pulse. Experiments were also conducted in which two control Ca 2ϩ transients were evoked by caffeine in buffer without ethanol, phloretin, or phloridzin to ensure that there were no significant changes in amplitude and/or area without the addition of drug (also see Kargacin et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of Ca 2ϩ uptake by tamoxifen was not mimicked by ␤-estradiol and ␤-estradiol did not alter the effects of tamoxifen (Kargacin et al, 2000;Dodds et al, 2001), indicating that the action of tamoxifen is not mediated by interaction with estrogen receptors. In previous work with phytoestrogens, it was shown (Shoshan and MacLennan, 1981) that quercetin directly inhibits the ATPase activity of the SR Ca 2ϩ pump.…”
mentioning
confidence: 93%
“…In previous studies (Kargacin et al, 2000;Dodds et al, 2001), we showed that the mixed estrogen antagonists/agonists tamoxifen, 4-hydroxytamoxifen, and clomiphene inhibit Ca 2ϩ uptake into cardiac sarcoplasmic reticulum (SR). Inhibition of Ca 2ϩ uptake by tamoxifen was not mimicked by ␤-estradiol and ␤-estradiol did not alter the effects of tamoxifen (Kargacin et al, 2000;Dodds et al, 2001), indicating that the action of tamoxifen is not mediated by interaction with estrogen receptors.…”
mentioning
confidence: 99%